The microstructure approach to exchange rates - Lyons, Richard K. (Cambridge: MIT Press, 2001)
The book shows how exchange -rate behavior previously thought to be particularly puzzling can be explained using the microstructure approach.
Includes bibliographical references and index
osa07/09/16
Loans
Keywords: Foreign exchange rates - mathematical models; Exchange rates - microstructure